Thermohydraulic and Economic Evaluation of a New Design for Printed Circuit Heat Exchangers in Supercritical CO2 Brayton Cycle (2023)
The present study focused on the analysis of a new geometrical modification of the conventional zig-zag channel for Printed Circuit Heat Exchangers. The research was carried out using OpenFOAM and Salome software, which were used for the CFD analysis and the construction of the computational domain. For the development of the study, three types of channel geometries were defined: a modified zig-zag channel, a conventional zig-zag channel, and a straight channel. The results show that the modified zig-zag channel achieves better thermal hydraulic performance compared to that of the conventional zig-zag channel, evidenced by a 7.6% increase in the thermal performance factor. The modified zig-zag channel proposed in the research caused a 1.5% reduction of the power consumption of supercritical Brayton cycle compressors. Additionally, the modified zig-zag channel achieves a maximum efficiency of 49.1%, which is 1.5% higher compared to that of the conventional zig-zag channel. The above results caused a 20.9% reduction of the operating costs of the supercritical Brayton cycle. This leads to a 5.9% decrease in the cost associated with using the PCHE compared to that of the conventional zig-zag channel. In general, the new geometric characteristics proposed for the conventional zig-zag channel minimize the high loss of the hydraulic performance without significantly compromising its heat transfer capacity. The geometric analysis of the proposed new zig-zag channel geometry was limited to evaluating the influence of the bend angle of 20–30◦ . Therefore, a more detailed geometric optimization process involving other geometric parameters of the channel is still needed. Future research will be focused on addressing this approach